2016
DOI: 10.1371/journal.ppat.1006115
|View full text |Cite
|
Sign up to set email alerts
|

Tolerogenic Plasmacytoid Dendritic Cells Control Paracoccidioides brasiliensis Infection by Inducting Regulatory T Cells in an IDO-Dependent Manner

Abstract: Plasmacytoid dendritic cells (pDCs), considered critical for immunity against viruses, were recently associated with defense mechanisms against fungal infections. However, the immunomodulatory function of pDCs in pulmonary paracoccidiodomycosis (PCM), an endemic fungal infection of Latin America, has been poorly defined. Here, we investigated the role of pDCs in the pathogenesis of PCM caused by the infection of 129Sv mice with 1 x 106 P. brasiliensis-yeasts. In vitro experiments showed that P. brasiliensis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 73 publications
5
42
0
1
Order By: Relevance
“…Unstimulated or alternatively activated pDCs are able to induce T cell tolerance to tumor cells, harmless antigens and alloantigens, primarily through the induction of regulatory T cells (Tregs) [109][110][111][112]. pDCs induce tolerance by expressing indoleamine 2,3-dioxygenase (IDO) [113][114][115], inducible T cell costimulator ligand (ICOSL) [109], tumor necrosis factor ligand superfamily member 4 (TNFSF4; also known as OX40L) [116,117], PD-L1 [118] or GrB [119]. It has been reported that a fraction of pDCs found in tumor draining lymph nodes (TDLNs) express IDO and activate Tregs [113,115].…”
Section: The Multifaceted Function Of Plasmacytoid Dendritic Cells: Nmentioning
confidence: 99%
“…Unstimulated or alternatively activated pDCs are able to induce T cell tolerance to tumor cells, harmless antigens and alloantigens, primarily through the induction of regulatory T cells (Tregs) [109][110][111][112]. pDCs induce tolerance by expressing indoleamine 2,3-dioxygenase (IDO) [113][114][115], inducible T cell costimulator ligand (ICOSL) [109], tumor necrosis factor ligand superfamily member 4 (TNFSF4; also known as OX40L) [116,117], PD-L1 [118] or GrB [119]. It has been reported that a fraction of pDCs found in tumor draining lymph nodes (TDLNs) express IDO and activate Tregs [113,115].…”
Section: The Multifaceted Function Of Plasmacytoid Dendritic Cells: Nmentioning
confidence: 99%
“…For instance, lymphoid-derived plasmacytoid DCs (pDCs) have been suggested to have a role in antifungal immunity in a tissue-dependent manner. Whereas depletion of pDCs was shown to render mice more susceptible to invasive aspergillosis in one study [112], others have suggested that pDCs can mediate tolerance in vaginal candidiasis and in a model of lung infection with P. brasiliensis [113]. P. brasiliensis infection, for example, increased the number of pDCs expressing indoleamine 2,3-dioxygenase (IDO), an enzyme with immunoregulatory properties that drives regulatory T cell (T reg ) expansion [113].…”
Section: Dendritic Cellsmentioning
confidence: 99%
“…Whereas depletion of pDCs was shown to render mice more susceptible to invasive aspergillosis in one study [112], others have suggested that pDCs can mediate tolerance in vaginal candidiasis and in a model of lung infection with P. brasiliensis [113]. P. brasiliensis infection, for example, increased the number of pDCs expressing indoleamine 2,3-dioxygenase (IDO), an enzyme with immunoregulatory properties that drives regulatory T cell (T reg ) expansion [113]. Remarkably, dectin-1-mediated activation of pDCs has been suggested to promote Th2 responses, while dectin-1 activation on myeloid DCs decrease Th2 responses upon β-glucan challenge.…”
Section: Dendritic Cellsmentioning
confidence: 99%
“…Furthermore, a reduced number of Foxp3 + Treg cells and decreased presence of pDCs expressing IDO were found in the lungs of pDC-depleted mice. Strong evidence for the role of IDO expression in the expansion of Treg cells was obtained using an in vitro experiment: pDCs of IDO-deficient mice and 1MT-treated pDCs of WT mice stimulated by P. brasiliensis yeast were more efficient at the induction and activation of T cells with concomitant reduction of Treg cells [121]. No surprises came out when we further explored the regulatory mechanism exerted by IDO-1 in the early and late phases of immunity against P. brasiliensis infection using IDO-1 −/mice.…”
Section: Regulatory T Cells In Murine Pcmmentioning
confidence: 99%
“…This type of immunity is the worst scenario for a host response to a pathogen, where uncontrolled fungal growth is accompanied by intense but inefficient inflammatory reactions causing exaggerated tissue pathology that ultimately leads to the accelerated death of infected mice [122]. Both studies showed that the IDO/ Treg/Th17 axis plays important roles in the control of immunity and the severity of pulmonary PCM [121,122].…”
Section: Regulatory T Cells In Murine Pcmmentioning
confidence: 99%